Efektivitas Terapi Target Sorafenib dalam Penanganan Hepatocellular Carcinoma: Literature Review - Dharma, Herbert; Purnamawati; Angeline, Reni (Jurnal MedScientiae, 2024)
Liver cancer is the sixth most common cancer and the third leading cause of death in the world. The main cause of liver cancer is the Hepatitis B or Hepatitis C virus which causes patient to experience chronic liver disease which can worsen and develop into liver cancer. Sorafenib targeted therapy can be used to treat patients with advanced liver cancer. This drug can suppress tumor cell proliferation and inhibit tumor angiogenesis. This study aims to determine the benefits of targeted therapy in treating Hepatocellular Carcinoma. The method used in this study is by searching for articles in electronic databases via the internet using Google Scholar and Pubmed. The results showed that the combination of sorafenib targeted therapy with conventional therapy, such as TACE and radiofrequency ablation, could significantly increase survival rates and time to progression. In conclusion, sorafenib targeted therapy when combined with conventional therapy has higher benefits and effectiveness compared to other therapies. The disadvantage of sorafenib targeted therapy is that it can cause many side effects for the patients.